The Vice of Luxury : Economic Excess in a Consumer Age - Cloutier, David, 1972- (Book collections on Project MUSE., 2015)
The problem of luxury has been neglected in contemporary Christian theology and philosophy, as well as in the broader social debate about the morality of our common economic life. And according to moral theologian David Cloutier this neglect of luxury has had harmful consequences: Greco-Roman and Judeo-Christian traditions are filled with critiques of luxury as a vice that is destructive both to individual persons and to society. Current and recent studies of economic ethics focus on the structural problems of poverty, of international trade, of workers' rights--but rarely if ever do such studies speak directly to the excesses of the wealthy, including the middle classes of advanced economies. What happened? Why has the unquenchable pursuit of a luxury lifestyle gotten a free pass? In interpreting luxury as a moral problem, Cloutier proposes a new approach to economic ethics that moves beyond pro-market v. anti-market screeds and focuses attention on our everyday economic choices. In Part 1 he surveys the history of Christian attitudes toward luxury and greed and provides a primer on economics; in Part 2 he examines the meaning of luxury and how to develop a prudential ethic of consumption that is compatible with Christian morality.